Using Vascular Plants as a Surrogate Taxon to Maximize Fungal Species Richness in Reserve Design - Chiarucci, Alessandro; D'AURIA, FRANCESCA; de Dominicis, Vincenzo; LAGANÀ, ANGELA; PERINI, CLAUDIA; SALERNI, ELENA (Conservation Biology, 2005)
Abstract: Fungi are a hyperdiverse taxonomic group that may be disappearing at a very high rate. Identifying fungal species is difficult in the field, and the use of highly specialized taxonomists is required. Data and expertise on vascular plants are, on the other hand, much more common and easy to find. We tested the potential of using vascular plants as surrogates to select reserve sites that maximize the pooled number of fungal species. We used data from 25 forest plots in Tuscany, Italy, that were sampled for woody plants, all other plants, and fungi. Species richness of woody plants and all other plants did not correlate with species richness of fungi. The gradients in species composition were similar among the three considered groups, as indicated by a detrended correspondence analysis ordination and species complementarity between pairs of plots. Fungal communities of the 25 plots had a lower β diversity than plant communities, and there were no pairs of totally complementary sites. Site prioritization for conservation was obtained through integer linear programming to find for any given number of sites those combinations containing the maximum pooled species richness of woody plants or all plants. The combinations of sites obtained by optimizing vascular plant species did not maximize the pooled species richness of fungi, whereas those obtained by maximizing woody plant species provided better results for sets of four to eight plots, but not for all the possible combinations. These results indicated that, in general, vascular plants cannot be used to maximize fungal species richness.
Keywords: fungi; species richness (voyant)